Air Pollution and the Risk of Parkinson's Disease: A Review. Issue 5 (19th January 2022) - Murata, Hiromi; Barnhill, Lisa M.; Bronstein, Jeff M.
ABSTRACT: Parkinson's disease, as well as other neurodegenerative disorders, are primarily characterized by pathological accumulation of proteins, inflammation, and neuron loss. Although there are some known genetic risk factors, most cases cannot be explained by genetics alone. Therefore, it is important to determine the environmental factors that confer risk and the mechanisms by which they act. Recent epidemiological studies have found that exposure to air pollution is associated with an increased risk for development of Parkinson's disease, although not all results are uniform. The variability between these studies is likely due to differences in what components of air pollution are measured, timing and methods used to determine exposures, and correction for other variables. There are several potential mechanisms by which air pollution could act to increase the risk for development of Parkinson's disease, including direct neuronal toxicity, induction of systemic inflammation leading to central nervous system inflammation, and alterations in gut physiology and the microbiome. Taken together, air pollution is an emerging risk factor in the development of Parkinson's disease. A number of potential mechanisms have been implicated by which it promotes neuropathology providing biological plausibility, and these mechanisms are likely relevant to the development of other neurodegenerative disorders such as Alzheimer's disease. This field is in its early stages, but a better understanding of how environmental exposures influence the pathogenesis of neurodegeneration is essential for reducing the incidence of disease and finding disease‐modifying therapies. © 2022 International Parkinson and Movement Disorder Society Abstract :